Review of Islamic Criminal Law on Perpetrators of Falsifying Death Certificates for Personal Profit - Syaddan dintara lubis; Muhammad bunayya alarrafi (Journal Equity of Law and Governance, 2024)
Basically, every one of us is a religion and of course every religion teaches goodness. Lying and lying is an act of lying and causing harm to oneself and even others. Therefore, this research is carried out to find out which Islamic law regulates the handling of the crime of forging death certificates and how positive laws regulate and handle the perpetrators of the crime of forging letters, which based on the research carried out the crime of forging death certificates can cause various losses to the victims, where the victims of this crime are not only the community but can causing losses to the government or the company. In Islamic law, criminal acts that cause harm to others are categorized as Jarimah acts with punitive sanctions in the form of ta'zir The rules based on positive law have been regulated in article 263 of the Criminal Code in the imposition of sanctions for perpetrators who forge or use fake letters as mentioned in paragraphs 1 and 2.